Naringenin Protects against Hypertension by Regulating Lipid Disorder and Oxidative Stress in a Rat Model - Hui Liu; Hui Zhao; Jingjin Che; Weijie Yao (Karger Publishers, 2022)
Background: Naringenin, a natural resource-derived flavanone, exhibits a plethora of pharmacological properties. The present study aimed to investigate the effects of naringenin on obesity-associated hypertension and its underlying mechanism. Methods: Obesity-associated hypertension rat model was established with a high-fat diet (HFD) and was administrated with naringenin (25, 50, 100 mg/kg). Body and fat weights were recorded and blood pressure was measured. Serum lipid parameters (cholesterol, low-density lipoprotein [LDL], high-density lipoprotein [HDL], and triglycerides), oxidative stress biomarkers (malondialdehyde [MDA], superoxide dismutase [SOD], nitrite oxide [NO], and glutathione [GSH]), and adipocytokines (leptin and adiponectin) were determined. The expressions of signal transducer and activator of transcription (STAT) 3 were determined by using Western blotting. Results: Treatment with naringenin (100 mg/kg) reduced body and fat weight in HFD-induced rats. Besides, treatment with naringenin (50 and 100 mg/kg) reduced blood pressure and regulated lipid parameters by decreasing cholesterol, triglycerides, and LDL and increasing HDL. Treatment with naringenin (50 and 100 mg/kg) reduced serum MDA and NO, whereas it increased serum SOD and GSH. Furthermore, treatment with naringenin (50 and 100 mg/kg) regulated adipocytokines and decreased the phosphorylation of STAT3. Conclusion: Naringenin ameliorates obesity-associated hypertension by regulating lipid disorder and oxidative stress.